Energy audit in residential building – replacement of portable air conditioner by an energy efficient centralised air conditioner. Issue 2 (28th January 2020) - Balan, K. N.; Yashvanth, U.
ABSTRACT: This article deals with the energy audit in the residential building in OMR, Chennai (latitude and longitude are: 13.067439, 80.237617), India. The present article aims to identify the inefficient electrical utilities in operation such as washing machine, refrigerators, air conditioners and major lighting equipment; based on the collected data, the decision will be made to replace them or service them. The collected data suggest that the air-conditioner unit consumes the 24% of daily total power consumption of the residential building. It is decided to modify the existing air-conditioning arrangement by the energy-efficient system without compromising human comfort. The audit team strongly recommends replacing the individual A/C systems such as window and splitting A/C systems by the centralised air-conditioner unit.